Corporate governance practices of insurance companies: attributes and accountability - Zatul Karamah Ahmad Baharul-Ulum; Syed Azizi Wafa Syed Khalid Wafa; Mohd Rahimie Abd Karim; Amer Azlan Abdul Jamal (Institute of Chartered Financial Analysts of India (ICFAI) University Press, 2014)
The paper attempts to examine the influence and relationship of corporate governance attributes with regard to accountability of corporate governance practices for insurance companies in Labuan International Business and Financial Centre. The findings of the study reveal that rules and regulations disclosure practice, directors’ qualifications and experiences, and audit committee’s effectiveness are found to be the key factors that influence the corporate governance regime. In all, the paper concludes that there is substantial scope for improvement in the current practices and suggests that effective corporate governance system is crucial to enhancing the performance of a firm.